Stafne's Bone Defect Correlated with Submandibular Glands: A Case Report and CBCT and MRI Analysis - Antoine Berberi (Hindawi Limited, 2024)
Stafne's bone defect is a developmental anatomic bone defect in the lingual side of the mandible in the area of the mandibular angle that is filled with proliferation or translocation of adjacent structures such as salivary gland tissue. The etiology is still undefined, and two hypotheses are proposed: one is the glandular related to the submandibular or sublingual glands and the second is ischemic that affects the vascularization of the mandibular lingual. Usually, Stafne's bone defect is accidentally detected on panoramic radiographs during dental treatments as a well-limited radiolucency image with a clear peripheral regular condensation border, located below the mandibular canal. The differential diagnosis includes traumatic bone cyst, odontogenic and nonodontogenic cystic lesions, nonossifying fibroma, focal osteoporotic bone marrow defect, and other lesions. A case of Stafne's bone defect on a 60-year-old male patient extending in the lingual posterior part of the mandibular region was presented. The panoramic radiograph revealed a well-limited radiolucency image with a clear peripheral regular condensation border, located below the mandibular canal. The lesion was discovered in a routine radiographic exam: the cone beam computed tomography gave us more details about the localization, the shape and size, and the relation with the mandibular canal, and the magnetic resonance imaging identifies the nature of the inside soft tissue. The final diagnosis was a Stafne's bone defect resulting of a depression of the lingual cortical plate filled with expansion of the submandibular gland.